Pengaruh Motivasi Dan Manajemen Talenta Terhadap Pengembangan Karier Pegawai Di Badan Pemeriksa Keuangan Republik Indonesia - Mengkuningtyas, Yeni (Jurnal Ilmiah Administrasi Publik, 2021)
The purpose of this study is to determine the effect of motivation and talent management on the career development of employees at The Audit Board of the Republic of Indonesia partially and simultaneously. This research uses a quantitative approach and it is a survey research. The survey used a questionnaire and the data were processed using the Partial Least Square statistical application. The sampling method was simple random sampling and the total sample was 137 supervisory officials. The results showed that motivation had a positive and significant effect on career development (the value of Original Sample=0,800, TStatistic=14,141); talent management has no significant effect on career development (the value of Original Sample=-0,097, T-Statistic=1,518); and motivation and talent management effect on career development simultaneously (the value of Fcount=91,77, Ftable=3,91).